(H, Li)Cl and LiOH hydration : surface tension, solution conductivity and viscosity, and exothermic dynamics - Sun, Chang Qing (2020)
We systematically examined the effect of (H, Li)Cl and LiOH solvation on the O:H[sbnd]O bond network deformation, surface tension (contact angle), solution electrical conductivity, thermomics, and viscosity evolution aiming to clarifying the functionalities for ions, lone pairs, and protons acting in these solutions. Results confirmed that H + and electron lone pair ‘:’ introduction turns out the (H 3 O + , OH − )·4H 2 O motifs and that the Li + and Cl − form each a hydration volume through the screened electrostatic polarization. The (H 3 O + , OH − )·4H 2 O turns an O:H[sbnd]O bond into the H ↔ H anti–HB that disrupts the HCl solution network and its surface tension and into the O:⇔:O super–HB compressor that raises the LiOH solution surface tension and viscosity, as well as the solution temperature during solvation. The Li + /Cl − ion reserves/reduces its hydration volume because of the complete/incomplete screen shielding by the ordered hydrating H 2 O dipoles and the Cl − ↔ Cl − repulsion at higher concentrations. The invariant/variant Li + /Cl − hydration volume dictates, respectively, the linear/nonlinear concentration dependence of the Jones–Dole viscosity. Except for the HCl/H 2 O surface tension and LiOH/H 2 O viscosity, the conductivity, surface tension, and viscosity of these solutions follow the Jones–Dole notion that underscores the faction of bond transition from the mode of water to hydration.